A novel, label-free fluorescent aptasensor for cocaine detection based on a G-quadruplex and ruthenium polypyridyl complex molecular light switch. Issue 18 (22nd April 2016) - Zhang, Songbai; Wang, Linping; Liu, Meiling; Qiu, Yanqing; Wang, Mengna; Liu, Xuewen; Shen, Guoli; Yu, Ruqin
Abstract : A [Ru(bpy)2 (bqdppz)] 2+ ligand with high selectivity towards G-quadruplex was synthesized and introduced to serve as a prominent molecular light switch via specifically recognizing the cocaine aptamer-involved G-quadruplex. Abstract : In this report, a novel, label-free fluorescence aptasensor for cocaine was developed based on a G-quadruplex and ruthenium(ii ) complex molecular light switch. A Ru[(bpy)2 (bqdppz)] 2+ ligand with high selectivity towards G-quadruplex was synthesized and introduced to serve as a prominent molecular light switch via specifically recognizing a cocaine aptamer G-quadruplex. The one-step detection strategy was simply achieved by target-binding-triggered structural dissociation of G-quadruplex accompanied by the sufficient release of Ru-ligand and significant decrease of fluorescent signal. A linear response was obtained over the range of 12–1300 nM, with a low detection limit of 5 nM. The proposed aptasensing method possesses the advantages of speed, easy preparation, being label-free, high sensitivity and low cost.